Public Speaking Skills as a Prerequisite to Implementation Field Experience Practice of Physical Education Sport & Health Teachers - Wicahyani, Sri; Kristiyandaru, Advendi; Kartiko, Dwi Cahyo; Williyanto, Septian; Pardiman, Pardiman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this study is to analyze the role of public speaking skills in preparation for field experience practice programme especially prospective of Physical Education Sport & Health teachers. The field experience practices is the programme expecting to form the prospective teachers who have the competencies required to become professional Physical Education Sport & Health teachers. The method used is descriptive qualitative by conducting a study of earlier research literature with the criteria for selecting articles based on PICOT. PICOT criteria consist of population, intervention, comparison, outcome and time. The results of the study show that public speaking skills play an important role on implementation of field experience practice for mastering the class with vocals and manage the class from the opening of the lesson to the closing activity. In addition, public speaking skills are useful for other incidental activities at school. For example are leading a meeting, being an MC (master of ceremonies) at special events at school, art performances, sports championships, etc. This research concluded that the mastery of public speaking skills is very important as a prerequisite for field experience practice prospective of Physical Education Sport & Health teachers before being sent to practice school.